Physician Workforce Diversity and Health Equity: It Is Time for Synergy in Missions! - Said A. Ibrahim (Mary Ann Liebert, 2019)
Diversity in academic medicine has regressed for the past two decades and the number of underrepresented minority trainees committed to academic careers in the biomedical sciences remains a significant challenge. Marked disparities in health care access and outcomes by race, gender, geography, and wealth remain, in part driven by social determinants of health. Despite widespread recognition that workforce diversity plays an important role in reducing disparities in health and health care, medical schools have not always linked their diversity efforts with their health equity efforts. The misalignment in academic diversity building and health equity initiatives represents a missed opportunity for mission synergy.